2015
DOI: 10.1016/j.chb.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Life-span differences in the uses and gratifications of tablets: Implications for older adults

Abstract: This study extends Uses and Gratifications theory by examining the uses and gratifications of a new technological device, the tablet computer, and investigating the differential uses and gratifications of tablet computers across the life-span. First, we utilized a six-week tablet training intervention to adapt and extend existing measures to the tablet as a technological device. Next, we used paper-based and online surveys (N=847), we confirmed four main uses of tablets: 1) Information Seeking, 2) Relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 36 publications
(68 reference statements)
1
16
0
1
Order By: Relevance
“…It is possible that the decreased response rates for older patients is due to an unfamiliarity with using electronic tablets; this can in turn lead to a longer time to completion. 8,21 A longer time to completion would increase the likelihood for patients to be interrupted by clinical staff and taken to the examination room before finishing the PROMIS forms, a common complaint among our noncompliant patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the decreased response rates for older patients is due to an unfamiliarity with using electronic tablets; this can in turn lead to a longer time to completion. 8,21 A longer time to completion would increase the likelihood for patients to be interrupted by clinical staff and taken to the examination room before finishing the PROMIS forms, a common complaint among our noncompliant patients.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to behavioral intentions of users in computermediated environments, age has been one of the predominant factors exerting effects on a number of constructs such as self-efficacy, skill acquisition, trust, willingness to adopt, social/pragmatic dependency, and outcome expectations [44]. Prior research on online information seeking [56], cellular phones [18], tablet devices [44], and social networking sites [46][47][48], suggests that perceptions, usage, access, adoption, as well as diffusion of various technologies, vary substantially among younger and older age groups. Much of games research concentrates on studying adolescents and young gamers [9,11,59].…”
Section: Age Differencesmentioning
confidence: 99%
“…While the generational divide in mobile phone adoption may be shifting ( Gilleard, Jones, & Higgs, 2015 ; Taipale, Wilska, & Gilleard, 2018 ), age remains strongly, negatively correlated with technology adoption, including when comparing middle-aged adults’ use with older adults’ use ( Carr, Gotlieb, Lee, & Shah, 2012 ; Van Deursen & Van Dijk, 2014 ). Magsamen-Conrad, Dowd, Abuljadail, Alsulaiman, and Shareefi (2015) found that, compared with older adults, middle-aged adults are more active users of tablets to track healthy lifestyle habits, maintain social communication, prevent accidents, and seek information. Compared with their younger counterparts, older adults are also less likely to be active users of the Internet ( Friemel, 2016 ; Zickuhr, 2013 ).…”
Section: Empirical and Theoretical Frameworkmentioning
confidence: 99%
“…Nonetheless, when it comes to mobile phone use in particular (as opposed to technology more broadly), compared with younger users, older adults tend to be more likely to use mobile phones for their original design purpose—that is, making calls for instrumental reasons such as arranging plans and other instrumental activities rather than playing games, surfing the internet, or using auxiliary applications ( Magsamen-Conrad et al, 2015 ).…”
Section: Empirical and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation